For this case we must solve the following system of equations:
If we add both equations we have:
We find the value of the variable "y":
Thus, the solution of the system is (-2, -3)
ANswer:
(-2, -3)
Answer:
x = -2 and y = -3
Explanation:
It is given that,
-8x + 3y =7 ----(1)
13x - 3y =-17 -----(2)
To find the value of x and y
eq(1) + eq(2) ⇒
-8x + 3y = 7 ----(1)
13x - 3y = -17 -----(2)
5x + = -10
x = -10/5 = -2
Substitute value of x in eq (1)
-8 * -2 + 3y = 7
16 + 3y = 7
3y = 7 - 16 = -9
y = -9/3 = -3
Therefore x = -2 and y = -3
5.2m questions
6.8m answers